Strengthening the collaboration between the home and school in Kaisahan ng Magulang at Anak na May Kapansanan (KAISAKA), Inc. Malate, Manila - Gonzaga-Merida, Marina (2016)
This research investigated the home-school collaboration between the parents of children with disabilities and the school called Kaisahan ng Magulang at Anak na May Kapansanan (KAISAKA, Inc.) Malate, Manila, for the school year 2012-2013. It used the qualitative case study design. The following research instruments were used: checklist, rating scale, open ended questionnaire, and focus group discussions. The study was guided by the theory of Joyce Epstein (1995), "Sphere of Overlapping Influences, Model of Family Involvement". In this theory, Joyce Epstein showed that a high level of success can coordinate and work together to encourage students in their learning and development. This study showed that there was a high level or degree of participation in the collaboration between the parents/relatives and the KAISAKA, Inc. However, these strategies in collaboration need to be strengthened to further help achieve the highest possible levels of learning of students with disabilities. There is a plan of action recommended to further strengthen the collaboration between the parents/relatives and the KAISAKA, Inc.
Keywords: People with disabilities; Kaisahan ng Magulang at Anak na may Kapansanan (KAISAKA), Inc